The Vitamin D Intake, Probiotic Intake, and Infection Incidence and Nutritional Status in Children Aged 24–59 Months - Davidson, Sarah Melati; Tauho, Kristiani Desimina; Renyoet, Brigitte Sarah; Wijaya, Clarisa Dinda Putri (Sarana Ilmu Indonesia (salnesia), 2025)
Stunting remains a major nutritional problem among children in Indonesia. The 2022 SSGI reported a stunting prevalence of 21,6% nationally, 20,8% in Central Java Province, and 28,9% in Temanggung Regency. Vitamin D plays a role in bone growth and immune regulation, probiotics support gut microbiota balance and nutrient absorption, and infection incidence may affect nutritional status. This study aimed to examine the relationship between vitamin D intake, probiotic intake, and infection incidence with nutritional status (height-for-age) among children aged 24–59 months in Temanggung Regency. An analytical survey with a cross-sectional design was conducted in March 2024. The population consisted of all under-five children in Temanggung Regency, with 55 subjects selected through purposive sampling. Data were collected through direct height measurements and interviews using questionnaires, including 24-hour dietary recall, infection history, and supplement consumption. The results showed no significant association between vitamin D intake, probiotic intake, or infection incidence and height-for-age (p-value > 0,05). This may be influenced by recall bias and the lack of assessment of infection duration and frequency. Further studies should explore other risk factors contributing to stunting in Temanggung Regency.